2010
DOI: 10.1074/jbc.m109.069070
|View full text |Cite
|
Sign up to set email alerts
|

Conformation Change in a Self-recognizing Autotransporter Modulates Bacterial Cell-Cell Interaction

Abstract: Bacteria mostly live as multicellular communities, although they are unicellular organisms, yet the mechanisms that tie individual bacteria together are often poorly understood. The adhesin involved in diffuse adherence (AIDA-I) is an adhesin of diarrheagenic Escherichia coli strains. AIDA-I also mediates bacterial auto-aggregation and biofilm formation and thus could be important for the organization of communities of pathogens. Using purified protein and whole bacteria, we provide direct evidence that AIDA-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 42 publications
3
16
0
Order By: Relevance
“…The intercellular TibA-TibA interaction is also responsible for bacterial autoaggregation and biofilm formation (40). AIDA-I (adhesin involved in diffuse adherence 1) and other similar autotransporter adhesins also utilize a selfrecognition mechanism to form biofilms which may allow bacteria to switch from free-living to sessile biofilm lifestyles in their native ecological niches (14,40). All these observations are consistent with our hypothesis that the BapA1-BapA1 interaction contributes to bacterial autoaggregation and biofilm formation.…”
Section: Vol 79 2011supporting
confidence: 78%
See 1 more Smart Citation
“…The intercellular TibA-TibA interaction is also responsible for bacterial autoaggregation and biofilm formation (40). AIDA-I (adhesin involved in diffuse adherence 1) and other similar autotransporter adhesins also utilize a selfrecognition mechanism to form biofilms which may allow bacteria to switch from free-living to sessile biofilm lifestyles in their native ecological niches (14,40). All these observations are consistent with our hypothesis that the BapA1-BapA1 interaction contributes to bacterial autoaggregation and biofilm formation.…”
Section: Vol 79 2011supporting
confidence: 78%
“…Overnight cultures of different streptococcal strains were washed with PBS once, adjusted to the same optical density (OD 470 ϭ 1.9) in test tubes, and kept at 4°C for up to 30 h. The top half of the culture suspensions was sampled, the sample was transferred to a fresh test tube, and the OD value was measured at 470 nm for each sample (14). The experiments were repeated 3 times, and the data were analyzed using the TTEST program.…”
Section: Methodsmentioning
confidence: 99%
“…All mutants affected in these functionalities were also affected in either autoaggregation or adhesion. Similar observations were made in previous studies with AIDA-I (8,14) and Ag43 (21,35). This suggests that adhesion and autoaggregation are the main functions of SAATs, whereas biofilm formation and invasion are secondary to these two functions.…”
Section: Discussionsupporting
confidence: 76%
“…This low-salt medium was used for aggregation assays because we have observed that TibA-dependent aggregation, but not necessarily TibA expression, is progressively inhibited by increasing concentrations of NaCl. High salt concentrations have also been reported to disrupt self-interactions of AIDA-I, another autoaggregating adhesin of diarrheagenic E. coli (34). For qualitative comparisons, representative cultures of four or more independent replicates were photographed immediately after vigorous mixing and 3 h after standing at room temperature without agitation.…”
Section: Methodsmentioning
confidence: 99%